Post-traumatic tension pneumocephalus and cystic angiomatosis of the skull: case report - Haythem H. Osman (SpringerOpen, 2021)
Abstract Background Tension pneumocephalus is an increasing air trapped intracranially. Either spontaneous, post-traumatic or iatrogenic in origin. Cystic angiomatosis is a benign vascular hamartoma of the skeleton, when acquired it is either due to trauma or infection. This is the second report in English literature of post-traumatic delayed tension pneumocephalus with the development of cystic angiomatosis of the skull bone. Case presentation A 55-year-old gentlemen, presented with scalp swelling of 6-month duration with history of head trauma 2 years back. The swelling was increasing and associated with progressive walking difficulties and left hearing loss. CT scan and MRI revealed extradural pneumocephalus, parietal and occipital pneumatocele, and multiple lytic bony lesions, left mastoid hyperpneumatization with inner table defect communicating with the extradural space. Diagnosis of delayed extradural tension pneumocephalus was made. Surgical exploration revealed multiple bony defects of parietal, temporal and squamous part of left temporal bones, confirmed extradural pneumocephalus with intact dura. Repair of mastoid defect of (0.5 × 0.5 cm), excision of pneumatocele and removal of lytic bones were performed. Defective bone “cribriform-like” was identified at occipital and parietal regions centrally with a defect of nearly 7 × 7 cm. Future cranioplasty was considered after 6 months. Histology of bony chips and surrounding soft tissues is recognized as cystic angiomatosis. Conclusions The present case developed two very rare complications, following trivial head trauma; the first complication was delayed extradural tension pneumocephalus with pneumatocele which presented 2 years after trauma, the origin of air was from a defect of the inner table of the mastoid, the second complication was cystic angiomatosis of the skull bones. Both complications were managed surgically in one operative session as a combined neurosurgery and otolaryngology teams approach.